European federal criminal law : the federal dimension of EU criminal law / Carlos Gómez-Jara Díez. - Gómez-Jara Díez, Carlos (Intersentia, 2015)
For decades, the EU has developed a system of criminal justice consistent with the mixed (sometimes contradictory) tendencies embedded in its very own structure. The Lisbon Treaty consolidated some federal elements that have an impact on the future development of this area of law. The sovereign debt crisis of 2010 and its progeny have, if anything, consolidated the need for the federal protection of EU financial interests at the EU level. This book aims to provide new insights in the federal dimension of these developments. Beginning with an analysis of the current state of affairs, the book also tackles the federalizing elements contained in such issues as the creation of a European banking supervision authority, the establishment of the European Prosecutor Office or the enactment of a EU regulation containing the grounds rules of its functioning. Throughout the chapters the reader will find constant references to the most efficient system of federal criminal law, i.e. the US system. This comparative law note serves the purpose of confirming the federal nature of what has been achieved so far at the EU level and providing guidelines for its future development. The basic contention of this book is that such regulation and its enforcement at the EU level is a fundamental tool to achieve the goals that the EU has already set forth in the upcoming agenda. In a nutshell: although the EU is not a federal state, it has the same problems as if it were. '[T]he book's content is readily accessible even for non-specialists in EU or US law, thanks to the author's clear writing style. All the foundational concepts of both systems are explained and a very useful bibliography with the major reference books is included. The reasoning is clear and always follows the original dichotomy between horizontal and vertical federalism, even if the structuring of the chapters may be surprising [...] worth reading the whole book to truly appreciate the quality of this research that opens new perspectives about the evolution of European Criminal Law [...]' Louise Seiler in New Journal of European Criminal Law (2016) 495'[the] book deserves a lot of attention for its insight and novelty, especially from those constitutional/EU lawyers who are not yet fully aware of this branch of EU law.' Massimo Fichera in Common Market Law Review (2107) 967